English Translations of 15th and 16th-Century Latin Sources on Baltic Religion and Mythology - Racėnaitė, Radvilė (Tautosakos darbai, 2024)
Pagans in the Early Modern Baltic. Sixteenth-Century Ethnographic Accounts of Baltic Paganism, edited and translated from Latin by Francis Young, Leeds: Arc Humanities Press, 2022, 192 p., ISBN 978-1-64189-437-1